Implikasi Visi, Misi Dan Nilai-Nilai Organisasi Terhadap Kinerja Karyawan Restoran Numani - R. Jati Nurcahyo - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2014)
Abstract - The research is aim to investigate the understanding of Employment of Numani Restaurant on vision, mission and organizational values as well as implication on its business valuation and kompensasi system on supporting job performance. Based on qualitative analysis, the results emphasize the importance both the understanding of Employment of Numani Restaurant valuation and kompensasi system on supporting job performance.Keyword: vision, mission, organizational values, job performance.